Sirolimus as initial therapy for kaposiform hemangioendothelioma and tufted angioma - Wang, Huaijie; Guo, Xinkui; Duan, Yitao; Zheng, Baijun; Gao, Ya (Pediatric dermatology, 2018)
Background Sirolimus has been used to manage various complex vascular anomalies. Kaposiform hemangioendothelioma and tufted angioma may develop Kasabach‐Merritt phenomenon in infancy. Methods We retrospectively reviewed the clinical and laboratory data of eight patients with kaposiform hemangioendothelioma and tufted angioma who were initially treated using oral sirolimus in our center, including six with Kasabach‐Merritt phenomenon. Results Five girls and three boys seen between September 2012 and March 2015 were included. Age at initiation of sirolimus ranged from 30 days to 14 weeks (mean±SD 8.6 ± 3.5 weeks). Six of these eight patients had kaposiform hemangioendothelioma, and two had a tufted angioma. Platelet count before start of oral sirolimus ranged from 5 × 109/L to 189 × 109/L ((78.8 ± 65.2)×109/L) and fibrinogen level from 68 to 215 mg/dL (123.1 ± 50.5 mg/dL). All patients received standard doses of sirolimus (0.05 mg/kg orally, twice daily) as initial therapy. All patients with thrombocytopenia or hypofibrinogenemia reached a normal platelet count and a normal fibrinogen level within 3 to 4 weeks after sirolimus treatment. Length of treatment ranged from 12 to 79 weeks (39.9 ± 15.3 weeks). Two patients developed grade 2 oral mucositis during treatment. Conclusion Sirolimus as first‐line therapy shows great promise in the treatment of kaposiform hemangioendothelioma and tufted angioma.